Ligand engineering at the precursor stage unlocks exceptional durability in PtCo@PtAu catalysts for heavy-duty PEMFCs - Lee, Jiyeon; Park, Jae-Hyun; Choi, Daeil; Lee, Kyung Rok; Lee, Sehyun; Yoo, Sung Jong (Elsevier BV, 2026)
Developing robust and highly efficient catalysts for the sluggish oxygen reduction reaction is crucial for the commercialization of heavy-duty proton exchange membrane fuel cells (PEMFCs). Despite their outstanding activity, Pt and Pt metal alloys are vulnerable to harsh operating conditions, leading to performance degradation. In this study, we develop a facile strategy for synthesizing PtCo nanoparticles with PtAu shells via galvanic replacement using pH control. This strategy begins with the ligand exchange of the Au precursor and changes in its reduction potential, as confirmed by the UV-Vis spectra. Rational PtAu shell formation results in an outstanding stability and enhanced mass transfer, which is achieved by adjusting the oxophilicity of Pt and preventing the dissolution of surface atoms. In a single-cell test, PtCo catalysts with Au-alloy shells achieve 94 % and 80 % retention of the peak power density and ECSA after 30,000 cycles, respectively. Notably, in the high-current-density region, the presence of surface Au enhances mass transfer by reducing surface hydrophilicity, making the developed system highly suitable for heavy-duty vehicle applications. We propose a viable strategy for practical, next-generation nanocatalysts that can address scalability concerns and pave the way for developing commercial heavy-duty PEMFCs.